A Comparative Study on Academic Stress among Higher Secondary Students in CBSE and State Board of Education with Special Reference to Thrissur District - Krishnajaly , P.S. (International Journal of Psychosocial Rehabilitation, 2020)
Students these days face high stress. This may occur as a result of psychological, physiological and environmental causes. This study focuses to understand the academic stress among higher secondary students. High levels of academic stress lead to negative effects on children like lack of confidence, anxiety, depression, etc. It is hence important to understand the various factors causing academic stress which indeed helps to manage such stress. Academic stress differs by following many factors, one of the major factors being the board of the study. It is understood from the study that CBSE students face a higher level of stress than state board students. So the present study aims to focus on academic stress among higher secondary students in CBSE and state board of education of Thrissur district.